2010
DOI: 10.1007/978-1-60761-919-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, Biodistribution, and Efficacy of GPCR-Based Pepducins in Disease Models

Abstract: G protein-coupled receptors (GPCR) are a superfamily of receptors that are vital in a wide array of physiological processes. Modulation of GPCR signaling has been an intensive area of therapeutic study, mainly due to the diverse pathophysiological significance of GPCRs. Pepducins are cell-penetrating lipidated peptides designed to target the intracellular loops of the GPCR of interest. Pepducins can function as agonists or antagonists of their cognate receptor, making them highly useful compounds for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 46 publications
1
59
1
1
Order By: Relevance
“…With respect to FPR2, no such studies have been performed, but results with a novel cellpenetrating pepducin, presented in a recent publication, suggest some type of role for the third intracellular loop in FPR2 signaling (31). Pepducins are lipidated peptides designed to target signaling loops of a particular receptor, and they can act as intracellular inhibitors or activators of signal transduction for the targeted receptor, but note that the exact receptor domains or the precise mechanism for how these peptides activate cells is still unclear (34,39). It is of importance to have this in mind when discussing the recent data showing that a lipidated peptide fragment derived from the third intracellular receptor loop of FPR2 specifically activates cells expressing this receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to FPR2, no such studies have been performed, but results with a novel cellpenetrating pepducin, presented in a recent publication, suggest some type of role for the third intracellular loop in FPR2 signaling (31). Pepducins are lipidated peptides designed to target signaling loops of a particular receptor, and they can act as intracellular inhibitors or activators of signal transduction for the targeted receptor, but note that the exact receptor domains or the precise mechanism for how these peptides activate cells is still unclear (34,39). It is of importance to have this in mind when discussing the recent data showing that a lipidated peptide fragment derived from the third intracellular receptor loop of FPR2 specifically activates cells expressing this receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…36 Pepducins have high bioavailability, efficacy, and long biologic half-lives when delivered systemically. 37 Cell-penetrating pepducins have been designed to target several GPCRs and exhibit in vivo efficacy in several disease models, including inhibition of cancer cell metastasis, 35,38 thrombosis, 29,32 and sepsis. 33,39 Our previous work demonstrated that CXCR4 pepducin antagonists were potent inhibitors of calcium mobilization and chemotaxis of human neutrophils in response to CXCL12 and could mobilize immature neutrophils to the peripheral blood of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Libraries of pepducins can be readily targeted to a GPCR of interest based on the sequences of the intracellular loops, including orphan GPCRs, and tested for allosteric activity by high throughput screening (15,16). This approach has proven useful in delineating the functional significance of GPCRs in cancer (17)(18)(19)(20) and cardiovascular (6,(21)(22)(23)(24) and inflammatory diseases (25)(26)(27)(28), and now pepducins have just entered human clinical trials (29); however, their mechanism of activation is largely unknown. Here, we define the structure of a PAR1 agonist pepducin, P1pal-19, that together with biochemical analyses and assays that monitor conformational changes reveal an allosteric activation mechanism for pepducins at the receptor-G protein interface.…”
mentioning
confidence: 99%